2023
DOI: 10.33225/jbse/23.22.37
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Multimedia Usage in Teaching and Learning Quantum Physics: Post-Assessment

Abstract: The research on students’ perceptions after implementing a teaching style is recommended due to its potential to inform reformed education. The present study surveyed 319 students and revealed their perceptions of multimedia usage in teaching and learning quantum physics. Among these students, 156 were surveyed after learning quantum physics with a multimedia-aided method, while 163 were surveyed after learning with a lecture method. The piloting of the test used generated Cronbach alpha of .841 of internal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Abstrak dari setiap artikel dibaca untuk menyusun daftar artikel yang terkait dengan topik utama, yaitu Quantum Teaching dan penerapannya. (Nyirahabimana et al, 2023) Artikel yang menjadi pusat perhatian dalam penelitian ini adalah artikel yang secara spesifik membahas Quantum Teaching. Dalam rangka penelitian ini, sebanyak 51 artikel dari berbagai jurnal telah dievaluasi.…”
Section: Pemilihan Artikelunclassified
“…Abstrak dari setiap artikel dibaca untuk menyusun daftar artikel yang terkait dengan topik utama, yaitu Quantum Teaching dan penerapannya. (Nyirahabimana et al, 2023) Artikel yang menjadi pusat perhatian dalam penelitian ini adalah artikel yang secara spesifik membahas Quantum Teaching. Dalam rangka penelitian ini, sebanyak 51 artikel dari berbagai jurnal telah dievaluasi.…”
Section: Pemilihan Artikelunclassified
“…The difference between end-of-chapter problems and inquiry activities used as homework was investigated by Simić et al (2023), who found that simulation-based and video-based homework contributes to the improvement of conceptual understanding in mechanics. The role of multimedia (simulations, animations, videos, models) in teaching university students black body radiation, photoelectric effect and other quantum physics topics is discussed by Nyirahabimana et al (2023). Interesting factors related to the social responsibility of scientists and engineers, as viewed by pre-service physics teachers, are analysed by Zhang (2023).…”
Section: Teaching Physicsmentioning
confidence: 99%